Editorial: Religiosity, Spirituality, and Ideology (Al-Jamiah Research Centre, 2012)
The current edition of Al-Jamiâah: Journal of Islamic Studies throws light on various themes related to contemporary development of Islamic religiosity with its multiple contexts. Indeed, Islam has become inspirations for many who uphold its dogma. Muslims, like any other who embrace other faiths, have participated in the creation of various traditions along human history. The first article, penned by Octavia with the title âIslamism and Democracy: a Gender Analysis on PKSâs Application of Democratic Principles and Values,â focuses on the internal dynamic within the Prosperous Justice Party (Partai Keadilan Sejahtera/PKS) with regard to the way in which the group has dealt with gender issues. The author detects the internal development of the PKS in which its activists responded to the gender issues in two ways. The first group remains conservative in line with Islamist ideology. The second group seems to start looking at the issue in a rather progressive way. Whereas the conservative wing displays their ideological stance, the progressive wing exhibits pragmatic step in response to the demand of the current context. After all, this shows ambiguity in the partyâs position pertaining to gender issues.